Flexible platforms for natural orifice transluminal and endoluminal surgery - Patel, Nisha; Seneci, Carlo; Yang, Guang-Zhong; Darzi, Ara; Teare, Julian (Endoscopy International Open, 2014)
The flexible endoscope is playing an increasingly pivotal role in minimally invasive transluminal and endoluminal surgery. Whilst the flexible nature of the platform is desirable in order to navigate through the abdominal cavity or through a lumen, there are a number of issues with using the platform for this purpose.The challenges associated with using flexible endoscopes such as a lack of triangulation of instruments and force transmission, which is often inadequate for endoscopic surgery are discussed in this review.As a result of these difficulties, a number of mechanically and robotically driven devices based upon the flexible endoscope are emerging. The design of these devices and potential problems are also reviewed. Finally, future robotic systems which are still in the development and validation stage are briefly discussed.The field of gastroenterology is diverging. The narrowing divide between minimally invasive and endoluminal surgery has led to a surge of innovative and novel devices which may in the future enable precise, seamless and scar less surgery.